IMPLEMENTASI K-MEANS CLUSTERING DENGAN MENGGUNAKAN DATA TRANSAKSI PENJUALAN UNTUK PENENTUAN REWARD PADA AGEN AQUA DAN GAS LPG FF TIRTA - Refika Ayuna Sari (2022)
Agent Aqua and LPG is one of the agents located on Jalan Radar Baru Rt 04 Rw 04, Kel. Kalisari, Kec. Pasar Rebo, East Jakarta, DITHUBAD shopping complex. The agent is one of the agents engaged in the sale of aqua and LPG gas. Considering that there are many business competitors in the same business, the agent owner must be able to make efforts to prevent customer switching, because satisfied customers can provide many benefits for the agent such as enabling the achievement of customer transaction targets. The target customer for the Aqua and LPG Gas Agent is very important because competition between similar companies may occur and result in a loss of customer satisfaction. Therefore, the owner will give gifts in the form of rewards to customers with a minimum purchase of more than 100 gallons and gas, but the problem that occurs at this time is that the agent owner does not know which customer has a minimum purchase of over 100 gallons and gas, so the agent owner has difficulty in giving rewards to these customers. Based on the explanation above, a research entitled "Implementation of K-Means Clustering Using Sales Transaction Data to Determine Rewards for Aqua and LPG Agents FF Tirta" with testing using the Davies-Bouldin Index (DBI) was carried out to prove that there are differences in settlement methods in determining the center of the cluster based on the number of squared errors. This research has the aim of building a system that can classify and determine the level of target customers based on purchase transactions so that agents can retain these potential customers by giving gifts in the form of special promos (rewards). The results of this research are there are groupings of customers who get rewards and cannot be seen monthly, namely in January there were 75 customers who got rewards and 100 did not get rewards, in February there were 70 customers who got rewards and 106 did not get rewards, in March there were 80 customers who got rewards and 96 did not get a reward, in April there were 35 customers who got the reward and 141 did not get the reward, in May there were 65 customers who got the reward and 111 did not get the reward, in June there were 43 customers who got the reward and 133 did not get the reward, in July there were 77 customers who got the reward rewarded and 99 did not receive a reward, in August there were 48 customers who